Problems with Time Limitation Regulation in the Settlement of General Election Offenses - Gaza Carumna Iskadrenda; Edward Omar Sharif Hiariej (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The electoral legal framework in Indonesia is designed to be highly complex, which causes several problems. One of them is in the realm of election offenses, considering the establishment of the settlement mechanism is complicated due to the very short time limit. This research aims to identify, examine, study, and discover many regulatory problems that will undoubtedly help law enforcers to settle election offenses in the future. This research falls under the category of normative legal research prioritizing the use of secondary data, including primary, secondary, and tertiary legal materials. Based on the data used, the documentation study/library study technique with tools in the form of written materials as described was used and qualitatively analyzed. The research finding showed that the specialization of the regulation in the form of speedy trial or fast-track judicial process is the root of the problem in the settlement of election offenses, considering the existing problems cannot be separated from it.